Foreign direct investment and the single market - Neary, J (Blackwell Publishing, 2002)
This paper extends the theory of multinational corporations, identifying three distinct influences of internal trade liberalization by a group of countries on the level and pattern of inward foreign direct investment (FDI). First, the tariff jumping motive encourages plant consolidation. Second, the export platform motive favours FDI with only a single union plant relative to exporting, and may induce a firm which has never exported to invest. Finally, reduced internal tariffs increase competition from domestic firms, which dilutes the other motives and may induce a ‘Fortress Europe’ outcome of multinationals leaving union markets even though external tariffs are unchanged.